Schooling for social justice, equity and inclusion : problematizing theory, policy and practice - Mifsud, Denise (Emerald Publishing Limited, 2024)
The ebook edition of this title is Open Access and freely available to read online. Discourses of social justice, equity and inclusion are often presented as given constructs to schools, with the expectation for school leaders to construct schooling provision and practices to 'solve' a wider societal, national, and global plaguing problem. While schools are crucial to ensure the provision of equitable education, they may also contribute, advertently or inadvertently, to the transformation of socio-economic inequalities into educational inequalities. Presenting theoretical pieces and case studies from Malta and Australia, in addition to using examples of applied social theory, such as Actor-Network Theory, Denise Mifsud unravels the conceptual confusion around the terms social justice, equity, and inclusion in relation to schooling and highlights the numerous persistent challenges faced when striving for equity in education. The critical conceptual arguments and empirical research presented in Schooling for Social Justice, Equity and Inclusion will be of interest to academics, policymakers, and practitioners in the educational policy and leadership fields internationally. Additionally, each chapter features pedagogical elements, including discussion questions and annotated bibliographies, that will help take the scholar experiment with novel methodologies and social theories and apply these to their own context while transporting them across disciplines in researching issues of social justice, equity and inclusion.
Keywords: Educational equalization.; Equality.; Education -- Philosophy, Theory & Social Aspects.; Educational strategies and policy: inclusion.; Philosophy and theory of education.; elektronické knihy; electronic books